(untitled) (Memorias Sifored - Encuentros Educación UAN, 2022)
Indigenous students linked to Higher Education in Colombia have had to face various challenges in times of pandemic due to the implications of virtual teaching. The objective of the investigative process reported in this presentation was to determine the recurring aspects that affected the training processes of two indigenous students linked to higher education. The methodology used is qualitative in the form of a case study and sought to understand the phenomenon from reflection on the sociocultural configuration of the students. The results obtained allow us to conclude that aspects such as the complexity with which the digital universe is configured, communication difficulties due to lack of mastery of the second language, the ontological configuration from materiality provided by the ancestral territories of the students and the insufficiency of technological resources, have hindered the training processes of these students in times of pandemic.